KORELASI PERKEMBANGAN MOTORIK DAN SOSIAL EMOSIONAL DENGAN DERAJAT STUNTING PADA BALITA - Lestaluhu, Santi Aprilian; Iswati, Ning; Blongkod, Fitriani Rahmatismi; Singkali, Dina Palayukan; Situmeang, Lamria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stunting is a condition in which the growth and development of a toddler is impaired due to long-term malnutrition, causing the child to be shorter in height than other children their age. Mauk sub-district still faces a serious problem related to the high stunting rate. Although handling efforts have been made, stunting cases in this area are still high. The purpose of the study was to determine the correlation of motor and social emotional development with the degree of stunting in toddlers. The study used quantitative research with a cross sectional design. The research was conducted in two stunting locus villages in Mauk District, Tangerang Regency. The research was conducted in November 2023. The study population was all stunted toddlers in the Mauk District area. The research sample amounted to 72 respondents. The sampling technique used purposive sampling. Data analysis was performed univariate and bivariate. The results showed there was a relationship between stunting on motor development (p value: 0.046) and social emotional development (p value: 0.035). It is recommended that parents of toddlers can do stimulus that can stimulate children's cognitive development. Stimulus carried out by parents must be done intensively so that there is an increase in child development slowly and for the Puskesmas to be able to provide counseling programs to posyandu cadres and the community regarding child development, how to stimulate it.Keywords: Toddler, Motor Development, Social-emotional Development, Stunting.